Measurement of the pseudoscalar decay constant fDs using Ds+→τ+ν, τ+→ρ+ν̄ decays - Naik, P; Rademacker, J; Asner, D; Edwards, K; Randrianarivony, K; Reed, J; Robichaud, A; Tatishvili, G; White, E; Briere, R; Vogel, H; Onyisi, P; et al. (2009)
Analyzing 600pb-1 of e+e- collisions at 4170 MeV center-of-mass energy with the CLEO-c detector, we measure the branching fraction B(Ds+→τ+ν)= (5.52±0.57±0.21)% using the τ+→ρ+ν̄ decay mode. Combining with other CLEO measurements of B(Ds+→τ+ν) we determine the pseudoscalar decay constant fDs=(259.7±7.8±3.4)MeV consistent with the value obtained from our Ds+→μ+ν measurement of (257.6±10.3±4.3)MeV. Combining these measurements we find a value of fDs=(259.0±6.2±3.0)MeV, that differs from the most accurate prediction based on unquenched lattice gauge theory of (241±3)MeV by 2.4 standard deviations. We also present the first measurements of B(Ds+→K0π+π0)=(1.00±0.18±0.04)%, and B(Ds+→π+π0π0)=(0.65±0.13±0.03)%, and measure a new value for B(Ds+→ηρ+)=(8.9±0.6±0.5)%. © 2009 The American Physical Society.